Visi Meningkatkan dan Memeratakan Mutu Pendidikan: Quo Vadis Transformasi Sekolah? - Siti Reni; Masduki Asbari; Mohamad Biazt Ramadhan (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to see the quality of improving the quality of education in Indonesia with the educational Transformation program. In this study report, a descriptive qualitative method is used by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Youtube Channel entitled